Quantification and assessment of changes in ecosystem service in the Three-River Headwaters Region, China as a result of climate variability and land cover change. (July 2016) - Jiang, Chong; Li, Daiqing; Wang, Dewang; Zhang, Linbo
Highlights: We studied changes of multiple ecosystem services and their synergies and trade-offs. We developed several methods to quantify ecosystem services in a spatially explicit manner. The soil conservation function of ecosystem was slightly enhanced from 2000 to 2012. Provisioning services (food production) increased significantly during 2000–2012. The net primary productivity and water yield increased substantially from 2000 to 2012. Abstract: Rapid and periodic assessment of the impact of land cover change and climate variability on ecosystem services at regional levels is essential to understanding services and sustainability of ecosystems. This study focused on quantifying and assessing the changes in multiple ecosystem services in the Three-River Headwaters Region (TRHR), China in 2000–2012. Based on the widely used biophysical models including Integrated Valuation of Ecosystem Services and Trade-Offs (InVEST), Revised Wind Erosion Equation (RWSQ), and Carnegie-Ames-Stanford Approach (CASA) models, this study assessed the historical flow of regulating services, including soil conservation, water yield, and carbon sequestration, and provisioning service food provision. The soil conservation function of ecosystem was slightly enhanced as a whole, and water yield increased sharply, with both the soil conservation and water yield showing an increasing spatial homogenization. The net primary productivity ( NPP ) and food production increased substantially from 2000 to 2012. Ecosystem services are closely and complexly interlinked. The correlation analyses indicated a trade-off between the water yield and carbon sequestration, however, a synergy between soil conservation and carbon sequestration. Congruence between the three different ecosystem provisioning services, including pasture, meat, and grain, was found. There was also a synergy between food production and ecosystem carbon sequestration in the TRHR. Climatic variability and vegetation restoration are important for the ecosystem services flow. Correlation analyses showed that the increase in precipitation significantly enhanced the water yield ( P  < 0.01) and soil erosion ( P  < 0.01), while the temperature increase influenced positively the NPP ( P  < 0.1). The experience of ecological rehabilitation and the change in key ecosystem services in the TRHR exemplified the positive effects of environmental policies and the necessity of adopting an adaptive management approach. Thus the ecological construction and policy making should take climate variability into account, and facilitate synergies on multiple ecosystem services in order to maximize human well-being and preserve its natural ecosystems.